2022
DOI: 10.3390/biom12020230
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Phytohormone-Producing Rhizobacteria on Casparian Band Formation, Ion Homeostasis and Salt Tolerance of Durum Wheat

Abstract: Inoculation with plant growth-promoting rhizobacteria can increase plant salt resistance. We aimed to reveal bacterial effects on the formation of apoplastic barriers and hormone concentration in relation to maintaining ion homeostasis and growth of salt-stressed plants. The rhizosphere of a durum wheat variety was inoculated with cytokinin-producing Bacillus subtilis and auxin-producing Pseudomonas mandelii strains. Plant growth, deposition of lignin and suberin and concentrations of sodium, potassium, phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 46 publications
(71 reference statements)
2
18
0
Order By: Relevance
“…These results demonstrate that Pseudomonas mandelii IB-Ki14 accelerated the formation of, and strengthened, apoplastic barriers. Previously, we detected that this microbe reinforced the apoplastic barriers in salt-stressed wheat plants [ 5 ], but the present research also confirms this effect under optimal conditions. Under salinity stress, the formation of apoplastic barriers is accompanied by a decrease in hydraulic conductivity [ 30 , 31 ], which limits the mass flow of toxic ions into the plant with the transpiration stream.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These results demonstrate that Pseudomonas mandelii IB-Ki14 accelerated the formation of, and strengthened, apoplastic barriers. Previously, we detected that this microbe reinforced the apoplastic barriers in salt-stressed wheat plants [ 5 ], but the present research also confirms this effect under optimal conditions. Under salinity stress, the formation of apoplastic barriers is accompanied by a decrease in hydraulic conductivity [ 30 , 31 ], which limits the mass flow of toxic ions into the plant with the transpiration stream.…”
Section: Discussionsupporting
confidence: 84%
“…Water flows through the plant depend on the hydraulic conductivity of the apoplast and cell membranes [ 4 ]. We recently demonstrated that Pseudomonas mandelii accelerated and enhanced the deposition of lignin and suberin and the formation of Casparian bands in the roots of salt-stressed wheat plants [ 5 ], which is known to promote salt tolerance in plants by limiting the penetration of toxic ions through the apoplast [ 6 ]. Since the formation of apoplastic barriers reduces hydraulic conductivity [ 7 ], it was important to check whether PGPR influence the formation of Casparian bands in the absence of salinity and how this affects the hydraulic conductivity of the roots.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research showed that many bacteria belonging to Bacillus could help maintain ion homeostasis in plants. For instance, Bacillus subtilis prevented the decline of K + concentration in salt‐treated durum wheat and Bacillus megaterium ZS‐3 can help the plant to limit excessive Na + uptake through downregulating HKT1 in Arabidopsis thaliana (Martynenko et al, 2022; Shi et al, 2022). The FaSOS1 gene encodes a Na + /H + antiporter NHX, which plays an important role in maintaining low Na + concentration and ion dynamic balance in the cytoplasm (Keisham et al, 2018; Zhang & Shi, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Bacillus subtilis enhanced the content of CKs in salt-stressed plants. The rhizospheric inoculation with CK-producing B. subtilis preceded an upregulation in the expression of a CASP-like protein gene 4D1, a part of the Casparian strip membrane domain protein group, resulting in an accelerated emergence of Casparian bands in root endodermis and improved growth of durum wheat variety in salt ( Martynenko et al., 2022 ). Elevated protein tyrosine nitration (PTN) is a well-established plant mechanism to salinity.…”
Section: Rhizospheric Microbiome As a Salinity-alleviating Agentmentioning
confidence: 99%
“…Ion homeostasis is a dynamic phenomenon, and its interruption is the fundamental reason for salinity’s growth-restricting action. Sodium and potassium ion competition for molecular transporters limits entry of the latter and disrupts plant metabolic activities ( Martynenko et al., 2022 ). Na + in roots is transferred from roots to aerial regions through xylem amid high salinity, where it deposits at leaf surfaces.…”
Section: Rhizospheric Microbiome As a Salinity-alleviating Agentmentioning
confidence: 99%